Corporate Restructuring at One of The Energy Companies in Indonesia: Does it Have an Impact? - Arum Puspitarini; Ruslan Prijadi (Eduvest - Journal of Universal Studies, 2023)
In 2021, one of Indonesia's state-owned enterprises (SOEs) in the energy sector, which is one of Indonesia's Fortune Global 500 companies, restructured and divided itself into six sub-holdings with distinct business segments. The company's corporate restructuring mechanism is financial and portfolio restructuring. Large corporations in Indonesia rarely engage in these corporate actions. Consequently, it is intriguing that this research examines the impacts of corporate restructuring. This study seeks to investigate the restructuring’s motives and the impacts of corporate reorganization on a company's performance, as well as its effect on the company's external environment. The authors utilized a qualitative approach with an explanatory case study to accomplish the research objectives. Individual depth interviews (IDI) are used to acquire data from multiple informants who represent shareholders, internal holding companies, and sub holding companies. This study provides an alternative assessment of the impacts of corporate reorganization so that both the company and the government can formulate future decision-making strategies. Most of the prior research on corporate restructuring employed an empirical quantitative technique approach, which involved analyzing data from a variety of companies and industries, so the results of the prior study lack comprehensive information.